PTU-132 Increased duodenal intra epithelial lymphocytes (IELS) are associated with recurrent abdominal pain and parasite infection but not Helicobacter pylori in a paediatric Chilean cohort. (28th May 2012) - Walker, M M; Rakhra, G S; Villagran, A; Harri, P R; Crabtree, J E
Abstract : Introduction: Functional Recurrent Abdominal Pain (RAP) is a paediatric functional gastrointestinal disorder with poorly investigated pathophysiology. Proposed aetiology varies and the diagnosis is characterised by Rome III criteria. Some studies consider Helicobacter pylori to be a cause of RAP, while others disagree. The aim of this study was to investigate upper gastrointestinal pathology in a cohort of 123 children in Chile with respect to RAP, H pylori infection and other concurrent infection. Methods: This blinded retrospective and IRB-approved study analysed biopsies taken from the gastric antrum and body and the duodenum in 123 Chilean children referred to endoscopy (with informed parental consent). Histopathology was evaluated against a clinical database which included symptoms, symptom duration and endoscopy findings. Rome III criteria were used to assign RAP to the relevant cases. All patients had stool microbiology and parasitology. H pylori infection was assessed by serology and histology. In the duodenum, routine histopathology and also eosinophil counts (in 5HPF ×40 magnification), were performed by microscopy. IELs/100 enterocytes were counted. Independently those patients with IELs >25 had serology performed for coeliac disease. Results: Overall 105 patients were diagnosed with RAP and 12 patients were able to act as controls, having no symptoms of RAP or concurrent infection. The Rome III diagnosis of RAP was significantly associated with higher IEL counts (>20 in 74 patients) compared to controls (p=0.04). Furthermore, a higher IEL count was also positively associated with parasitic infection (nine with parasites) (p=0.02). Of 16 patients with lymphocytic duodenosis, (>25 IELs per 100 enterocytes) only three were infected by H pylori . One had coeliac disease with positive serology. Antral nodularity was observed in association with lymphoid follicles (p≤0.01) and H pylori infection (p<0.01). 28% in this cohort were positive for H pylori but infection was not significantly associated with RAP (p=0.55) or parasite infection, as concurrent infection was present in only 2 patients (p=0.24). Conclusion: From this study, low grade inflammation, manifest by increased IELs, may be associated with RAP and also parasitic infection. H pylori is not associated with parasite infection. However, as eosinophilia was not significantly associated with the condition further investigation is required to elucidate the potential involvement of innate immunity, including mast cells. Furthermore, there is no association between H pylori infection and RAP. Funded by EU CONTENT Project (INCO-CT-2006-032136), CONICYT/BM (RUE #29) and Fondecyt #1100654 (Chile). Competing interests: None declared.